Many faces of malignant melanoma: Histopathological evaluation of liver biopsies - Selma Ş Erhan; Sevinç H Keser; Tülay T Keklik; Selvi D Tabak; Mehmet Özer (Wolters Kluwer Medknow Publications, 2022)
Background: Malignant melanoma (MM) is an aggressive tumor characterized by high metastatical potential and is sometimes diagnosed by distant organ metastasis such as liver. Morphologically it may mimic many other tumors and cause diagnostic challenges. In this paper, eleven MM cases metastasized to the liver with different morphologic patterns were analyzed in the light of literature. Materials and Methods: Histopathological and immunohistochemical findings of the cases diagnosed as MM metastasis in liver were reevaluated in the light of clinical data. Results: We obtained 11 MM cases with hepatic metastasis. In slides of the first four cases, morphologic features similar to epithelioid variant of MM with different amounts of melanin deposition were observed. In the fifth and sixth cases, fascicular patterned tumoral lesion composed of spindled cells were detected; and in the seventh and eighth cases, nested and sheet-like patterned tumoral lesion consist of giant bizarre and spindled cells with hyperchromatic nuclei were observed. The last three cases consisted of plasmacytoid cells with eccentric nuclei in pseudoalveolar pattern; and the exact diagnosis was possible with the help of immunohistochemistry. Conclusion: MM should always be kept in mind in differential diagnosis of metastatic hepatic tumors with unknown primary because of its various morphological characteristics.